DNA barcoding of class Aves using artificial neural networks - Chua, Ted Guillano S.; Santi, Nathan Lemuel G.; Sapasap, Ric Janus O. (2013)
DNA barcoding is currently used to classify species. The Mitochondrial Cytochrome Oxidase Subunit I (COI) gene is considered as the standard gene for the DNA barcoding of animals. DNA barcoding requires that the COI gene of the unknown DNA sequence be aligned first before classification. In the research, the unaligned COI genes are used to classify up to the taxonomic level of the family. The research is performed through the analysis of 17 families of the class Aves using the Fast Artificial Neural Network (FANN) library. Thirty sequences per family were used to train 30 different neural networks. All 2,548 available sequences were used to test the neural networks. The results show that unaligned codon classification has a mean percentage of 93.93%, a minimum percentage of 90.30%, and a maximum percentage of 96.46%. The results indicate that DNA classification without alignment is plausible.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman
Keywords: DNA fingerprinting; Molecular computers; Fast Artificial Neural Network (FANN).; Mitochondrial Cytochrome Oxidase Subunit I (COI).